An Analysis on the Impact of Participatory Budgeting and Procedura Fairness Toward Manager's Commitment and Performance - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
This study aims to test the effect of participatory budgeting and procedural fairness on the manager's commitment and performance either hove simultaneous or partial effect. The method of the research used was a survey method that conducted at the pawnshop in North Sumatra with the respondents of the managers in branch offices. The data used is primary data by collecting data through questionnaires. The analysis method used is descriptive-analytical verification. The effect model analyzed &sing a structural equation model to analyze the pattern of causal relationships Sween variables and determine the direct, indirect and total effect of some variables. The results showed that participatory budgeting ond procedural fairness simultanay have a significant and positive effect El the manager's commitment; participatory budgeting has a significant and positive effect an the manager's cammitmenb; procedural fairness has a significant andllsitive effect on the manager's commitment · articipatory budgeting, procedural fairness and manager's commitment simultaneously 'has a si :;: icant and positive effect on the manager's performance; the effect o participatory budgetin • as a significant and ositive effect on the anager's performance; hQrocedural fairness os a signi icanb and ositive effect an the manager's performance; the manager's commitment has a significant and positive effect on the na er's performance.